If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 * -2 + -3y = 6 Multiply -9 * -2 18 + -3y = 6 Solving 18 + -3y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -3y = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -3y = 6 + -18 -3y = 6 + -18 Combine like terms: 6 + -18 = -12 -3y = -12 Divide each side by '-3'. y = 4 Simplifying y = 4
| 9-3f=60 | | 5h+2(h-11)=-5 | | 7x=8x+-4 | | y=-16x^2-16x+5 | | 3x+12x-7=5x+3 | | X+19x=180 | | -16t^2+40t+40=0 | | (fg)(x)=-16x^2-16x+5 | | .10n+.25(n+5)=5.10 | | 3y+15=6x | | 5e+8=53 | | sinx=0.1 | | 4x-1=(15+2x) | | 71=-6(2-8x)+5(8x-1) | | 8x-24=8x+3(8+2x) | | 7-2exp(x)=0 | | 8x-12=-2(-4x+4) | | 73=-7x-3(-4x-16) | | e=6p-1x-2 | | .10+.25(n+5)=4.40 | | logx=3.6 | | 73=-7x-39(-4x-16) | | 75-10-8+12-18=x | | 5x+1/8=0.5 | | 5(x-6)=7x-6 | | exp(x)-2=4 | | 17+8=-3c-25 | | 36=5(3c-12)+4(2c+1) | | exp(7x)=8 | | 75-10-8+12=x | | 8x+4y=72 | | .10n+.25(n+6)=4.65 |